2022
DOI: 10.1021/acschembio.2c00679
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Labeling Fluorescent Probe Reveals Ectodomain Shedding of Transmembrane Carbonic Anhydrases

Abstract: Ectodomain shedding is a form of limited proteolysis in which a protease cleaves a transmembrane protein, releasing the extracellular domain from the cell surface. Cells use this process to regulate a wide variety of biological events. Typically, immunological detection methods are employed for the analysis of ectodomains secreted into the cultured media. In this paper, we describe a new strategy using an affinity-based protein-labeling fluorescent probe to study ectodomain shedding. We analyzed the ectodomain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…32 It has been shown previously that hCAIX undergoes ectodomain shedding by ADAM17 metalloprotease to release its soluble domain to extracellular media. 32,49,50 However, it is still unclear how hCAIX is degraded in the presence of ADAM17 inhibitors. In addition to probe 2, we also prepared probe 3 which contains a reactive NHS group for the nonselective covalent labeling of a large pool of membrane proteins on the cell surface.…”
Section: Fluorescent Tracking Of Protein Endocytosis and Ectodomain S...mentioning
confidence: 99%
See 1 more Smart Citation
“…32 It has been shown previously that hCAIX undergoes ectodomain shedding by ADAM17 metalloprotease to release its soluble domain to extracellular media. 32,49,50 However, it is still unclear how hCAIX is degraded in the presence of ADAM17 inhibitors. In addition to probe 2, we also prepared probe 3 which contains a reactive NHS group for the nonselective covalent labeling of a large pool of membrane proteins on the cell surface.…”
Section: Fluorescent Tracking Of Protein Endocytosis and Ectodomain S...mentioning
confidence: 99%
“…This problem is particularly severe for environment-sensitive PM dyes based on neutral hydrophobic dyes (e.g., NBD and Laurdan), which can be easily transported into the intracellular compartments by passive diffusion. Furthermore, it has also been reported that many cationic dyes (e.g., cyanines and rhodamines) can be rapidly transported through the plasma membrane by the flip-flop mechanism due to the transmembrane potential. , Therefore, these PM dyes often stain all intracellular lipid compartments rapidly, which hampers their applications for long-term live-cell plasma membrane imaging. Although several strategies have been reported to stain the plasma membrane with a prolonged retention period, including conjugated polymers, membrane protein covalent labeling probes, and zwitterionic fluorescent dyes, , these are either too large in size or require the cells to be genetically engineered to express the corresponding cell surface protein for labeling. Therefore, it is important to develop a small and biocompatible PM-targeted fluorescent dye with long retention time to allow a detailed study of the membrane dynamic activities in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report a new and rapid FRα protein-labeling fluorescent probe, FR1 , to study the expression and degradation of FRα in living cells (Figure a). The probe consists of a methotrexate ligand for FRα binding, a membrane-impermeable Cy5 fluorophore, and a reactive group based on a diflurophenyl ester moiety (Figure b). In the presence of FRα, the difluorophenyl ester group of FR1 can undergo a nucleophilic reaction to form a covalent bond with FRα via an amino acid residue close to the methotrexate binding site. With the labeling of FRα by FR1 , insights on the shedding and protein lifetime of FRα on the plasma membrane can be obtained using various biochemical techniques, such as fluorescence live-cell imaging and electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…To date, fluorescent probes are considered to be one of the most powerful tools for monitoring biological species in biological systems. On account of their desirable selectivity and sensitivity, excellent biocompatibility, and favorable spatial and temporal resolution, they have got a wide application in the CA detection. Up to now, dozens of different types of CA fluorescent probes have been reported, e.g., direct-conjugated recognition group on fluorophores; , one- or two-step photoaffinity probes; and one- or two-step electrophilic reaction probes. , However, in view of the availability, stability, and structural characterization clarity of CAs, most researchers regard CAs as model proteins for highlighting more modular research in probe designs. In addition, the emission wavelength of the existing CAs environment-sensitive probes is short, which limits the in-depth application of probes in living tissues. ,, A red or near-infrared fluorescent probe (>600 nm) allows penetration into deep tissues with little autofluorescence interference, which is suitable for imaging CAs in living cells or tissues and is an ideal choice for exploring biological systems. …”
mentioning
confidence: 99%